1997
DOI: 10.1016/s0735-1097(97)00228-3
|View full text |Cite
|
Sign up to set email alerts
|

Balloon Angioplasty of Recurrent Coarctation: A 12-Year Review

Abstract: Although the majority of patients undergoing percutaneous balloon angioplasty for recoarctation of the aorta will achieve long-term benefit, the need for further surgical intervention in those with transverse arch hypoplasia remains high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
92
1
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(108 citation statements)
references
References 38 publications
8
92
1
7
Order By: Relevance
“…A pressure gradient Ͼ20 mm Hg by catheterization has been proposed in numerous studies as an indication for surgical or balloon dilation of CoA and for the definition of procedural success. [1][2][3][4]6,7,27,28 The limitations inherent to relying on only one measurement of CoA severity, however, are recognized. .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pressure gradient Ͼ20 mm Hg by catheterization has been proposed in numerous studies as an indication for surgical or balloon dilation of CoA and for the definition of procedural success. [1][2][3][4]6,7,27,28 The limitations inherent to relying on only one measurement of CoA severity, however, are recognized. .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac catheterization with angiography and hemodynamic evaluation is considered the reference standard, and many published reports regard a transcatheter peak-to-peak pressure gradient Ն20 mm Hg as an important criterion for the diagnosis of hemodynamically significant CoA in the setting of normal cardiac index. [1][2][3][4][5][6][7][8] Several noninvasive methods have been used to assess the severity of CoA. Arm-to-leg blood pressure difference measured by sphygmomanometry can provide helpful information, but several reports have shown that it may not accurately represent the hemodynamic severity of the stenosis.…”
mentioning
confidence: 99%
“…[7][8][9] However, relapse after coarctation repair and complications related to surgical procedures are not uncommon, with aneurysm formation, stenosis, or occlusion of bypass grafts. 10 -12 Recurrent coarctation used to be the only late complication amenable to interventional treatment in lieu of surgical graft interposition or end-to-end anastomosis [13][14][15] ; postsurgical aneurysm may quality next for interventional repair.…”
Section: Discussionmentioning
confidence: 99%
“…The generally accepted criterion for intervention in a biventricular heart is a peak-to-peak gradient of 20 mm Hg [3,12,30,44]. This criterion, although arbitrary by itself, has been even more inappropriately applied to univentricular hearts, despite the fact that studies have shown that peak systolic gradients \20 mm Hg can cause significant diastolic dysfunction [23,41] [37].…”
mentioning
confidence: 99%